Pengaruh Motivasi Belajar Dan Disiplin Belajar Terhadap Prestasi Belajar Siswa SMA Swasta Se-Kecamatan Medan Marelan - Edy Wongaria (Jurnal Kajian dan Penelitian Umum, 2023)
The purpose of this study was to determine the effect of learning motivation and learning discipline on student achievement in private high schools throughout the district of Medan Marelan. The independent variable in this study is learning motivation (X1) and learning discipline (X2), and the dependent variable is learning achievement (Y). This study uses multiple regression analysis to determine the effect of learning motivation (X1) and learning discipline (X2), on learning achievement (Y). In this study, the determination of the sample used proportionate stratified random sampling with the number of samples used in this study as many as 156 respondents. This study uses primary data, data is collected by distributing questionnaires to respondents via google forms. Testing the research hypothesis using SPSS 20.0 for Windows. The results showed that learning motivation (X1) had a positive effect and significant on student achievement (Y) in private high schools throughout the district of Medan Marelan. Learning discipline (X2) has a positive effect on learning achievement (Y) of students in private high schools throughout the district of Medan Marelan. Learning motivation (X1) and learning discipline (X2) have a positive and significant effect together on learning achievement (Y) for private high school students in the District of Medan Marelan. The regression equation in this study is as follows: 1,2 = 26,818 + 0,290X1 + 0,579X2. Based on these results, to optimize learning achievement, it is necessary to have policies and regulations to increase learning motivation and learning discipline.